Hematological alterations and thymic function in newborns of HIV-infected mothers receiving antiretroviral drugs - Rotjanee Wongnoi (2018)
Objectives: To investigate the effects of antiretroviral (ARV) drugs on hematological parameters and thymic function in HIVuninfected newborns of HIV-infected mothers. Study design: Cross sectional study. Setting: Chiang-Mai University Hospital, Chiang-Mai, Thailand. Participants/Patients: 49 HIV-uninfected and 26 HIV-infected pregnancies. Methods: Cord blood samples of newborns from HIV-uninfected and HIV-infected mothers were collected. Hematological parameters were measured using automatic blood cell count. T-cell receptor excision circles (TRECs) levels in cord blood mononuclear cells (CBMCs), CD4 + and CD8 + T-cells were quantified using real-time PCR. Main Outcome Measures: Hemotological parameters and thymic function. Results: Newborn of HIV-infected mother tended to have lower mean levels of hemoglobin than those of HIV-uninfected mother (137 ± 22 vs 146 ± 17 g/L, P = 0.05). Furthermore, mean of red blood cell (RBC) counts and hematocrit and median of TRECs in CD4+ T-cells in the newborns of the former were significantly lower than those of the latter [3.6 ± 0.7 vs 4.8 ± 0.6 × 10 12 cells/L, P < 0.001; 0.40 ± 0.07 vs 0.46 ± 0.05 L/L, P < 0.001 and 0.53 (IQR: 0.03-5.76) vs 13.20 (IQR: 2.77-27.51) × 10 -3 pg/μL, P = 0.02, respectively]. Conclusion: ARV drugs altered hematological parameters and thymic function (TRECs CD4 + T-cells) in HIV-uninfected newborns of HIV-infected mothers. © 2013 Indian Academy of Pediatrics.